Development of EST-PCR Markers for the Chromosome 4V of Haynaldia villosa and Their Application in Identification of 4V Chromosome Structural Aberrants - Ren-hui ZHAO; Hai-yan WANG; Qi JIA; Jin XIAO; Chun-xia YUAN; Ya-jun ZHANG; Qing-shan HU; Xiu-e WANG (Journal of Integrative Agriculture, 2014)
EST-PCR based molecular markers specific for alien chromosomes are not only useful for the detection of the introgressed alien chromatin in the wheat background, but also provide evidence of the syntenic relationship between homoeologous chromosomes. In the present study, in order to develop high density and evenly distributed molecular markers on chromosome 4V of Haynaldia villosa, a total of 607 primer pairs were designed according to the EST sequences, which were previously located in 23 different bins of wheat chromosomes 4A, 4B and 4D. By using the Triticum durum-H. villosa amphiploid and T. aestivum-H. villosa alien chromosome lines involving chromosome 4V, it was found that 9.23% of the tested primers could amplify specific bands for chromosome 4V. Thirty and twenty-six specific markers could be assigned to chromosome arms 4VS and 4VL, respectively. These 4V specific markers provided efficient tools for the characterization of structural variation involving the chromosome 4V as well as for the selection of useful genes located on chromosome 4V in breeding programs.